Порівняльна адаптивна стратегія деяких інвазійних та індигенних видів - Мар'юшкіна, В.Я.; Гриценко, В.В.; Дідик, Н.П. (Український фітоценологічний збірник, 2006)
Рассматриваются проблемы адаптации адвентивных и аборигенных видов на примере Ambrosia artemisiifolia, Solidago canadensis, Elytrigia repens на различных уровнях (от фитоценоза до особи). Обсуждаются трудности исследований проблем адаптации на уровне фитоценоза. Однако этот подход может быть легко реализован если фитоценоз рассматривается как комплекс ниш ценопопуляций. Дальнейшие исследования должны включать анализ экологоценотических стратегий видов и детальный анализ ценопопуляций. Это подчеркивает подобие особи растения с модульным строением и популяции. Очевидно, подходы исследований на этих двух уровнях должны быть подобны также. Такие исследования должны заканчиваться изучением генетической структуры ценопопуляций. Такой детальный анализ необходим, если принять во внимание высокую агрессивность адвентивных видов. The problems of adaptations of invasive and indigenous species on the example of Ambrosia artemisiifolia, Solidago canadensis, Elytrigia repens at different levels (from the level of a phytocenosis to the level of an individual) are considered. The difficulties of investigations of problems of adaptations at the level of phytocenosis are discussed. Though the approach could be easily realized if the phytocenosis is considered as set of niches of cenopopulations. The further investigations should include analysis of ecologo-cenotic strategies of species and detailed analysis of cenopopulations. It is accentuated the similarity of plant individual with module organization to populations. Evidently, the approaches of investigations at these both levels should be similar too. It is appropriate to conclude such investigations with the studies of genetic structure of cenopopulations. Taking into account high aggressiveness of invasive species such detailed analysis is rather urgent.